Extended phantom sensation: vibrotactile-based movement sensation in the area outside the inter-stimulus. (4th March 2021) - Tawa, Syunsuke; Nagano, Hikaru; Tazaki, Yuichi; Yokokohji, Yasuyoshi
ABSTRACT: Vibrotactile phantom sensation is an intuitive methodology for perceiving the localization of a moving object. However, the presentation area is limited to the inter-stimulus. To extend the range of presentation beyond the inter-stimulus region, we attempted to establish a novel mathematical model for representing a wider range of phantom sensation than conventional models. The experiments 1-1 and 1-2 compared three methods (linear, exponential-like, and conventional inter-stimulus models). The results indicated that the proposed linear and exponential-like models effectively generated both the sense of outer and inner movement with and without training, and that the exponential-like model is best suited to represent accurate phantom sensations that cover the extended outer region. In experiment 2, we examined the effect of γ, a parameter related to the magnitude of exponential-like model damping, on presentation accuracy. The results showed that the high-dumping model ( γ = 2 ) showed high accuracy and suggested a trade-off between presentation accuracy and range. The findings of this study are expected to provide guidelines for the effective presentation of a wide range of phantom sensations occurring outside the inter-stimulus. GRAPHICAL ABSTRACT: UF0001